Analisis Pengaruh Penggunaan Arang Aktif Dari Cangkang Melo – Melo (Bailer Shell) Sebagai Media Penurunan Derajat Keasaman Pada Air Limbah Pencucian Timah - Dzuljalali, Muhammad; Ary Wahyudie, Ilham; Reza, Amril (Jurnal Inovasi Teknologi Terapan, 2024)
Polluted tin washing wastewater can be neutralized using activated charcoal made from clam shells. Clam shells are one of the materials that have a very high CaCO3 (calcium carbonate) content and are very effective in being used as an active charcoal material. Shells that have gone through the combustion process will become CaO (Calcium Oxide) and can become alkaline when dissolved with H2O (water) will produce Ca(OH)2 (Calcium Hydroxide) which is alkaline so that it can increase the pH quality of tin washing wastewater. Activated charcoal which has more open pores due to the combustion process, makes it stronger to absorb acid levels in tin washing wastewater in Air Nyatoh Village. In this study using the Taguchi method with Nominal is Best characteristics, the desired pH is pH 7.5 using matrix L9 (34) with factors namely Activated Charcoal Weight, Activated Charcoal Size, and Settling Time. Activated charcoal in this study uses Melo - Melo Clam Shells (Bailer Shell) that have been activated. After conducting the testing process, water that was originally at pH 4.0 experienced an increase to an average pH of 7.41. This is closer than the desired pH. Based on the calculations in this study, the weight of activated charcoal has an F Value of 23.56 and the size of activated charcoal has a value of 24.28. Both factors are the same - both have an influence on the increase in pH, while the deposition time has a value of 7.0 and has no effect on the increase in pH when measured against the F Table 5%, namely with a value of 19.00.